2012
DOI: 10.1016/j.bmc.2012.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Analogs of N′-hydroxy-N-(4H,5H-naphtho[1,2-d]thiazol-2-yl)methanimidamide inhibit Mycobacterium tuberculosis methionine aminopeptidases

Abstract: Our previous target validation studies established that inhibition of methionine aminopeptidases (MtMetAP, type 1a and 1c) from Mycobacterium tuberculosis (Mtb) is an effective approach to suppressing Mtb growth in culture. A novel class of MtMetAP1c inhibitors comprising of N'-hydroxy-N-(4H,5H-naphtho[1,2-d]thiazol-2-yl)methanimidamide (4c) was uncovered through a high-throughput screen (HTS). A systematic structure—activity relationship study (SAR) yielded variants of the hit, 4b, 4h, and 4k, bearing modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…One of the ser/thr kinases, protein kinase G (PknG), which plays a role in intracellular survival of mycobacteria in the host, has recently been used to identify the inhibitor AX20017 (Scherr et al 2007). Yet, in another study, it was shown that N′-hydroxymethanimidamide inhibitors have potent activity against the two methionine aminopeptidases of Mtb (Bhat et al 2012). These compounds did not become the lead inhibitors due to poor minimum inhibitory concentrations (MICs); however, it was suggestive that with certain modifications, new series of the inhibitors can be designed.…”
Section: Introductionmentioning
confidence: 97%
“…One of the ser/thr kinases, protein kinase G (PknG), which plays a role in intracellular survival of mycobacteria in the host, has recently been used to identify the inhibitor AX20017 (Scherr et al 2007). Yet, in another study, it was shown that N′-hydroxymethanimidamide inhibitors have potent activity against the two methionine aminopeptidases of Mtb (Bhat et al 2012). These compounds did not become the lead inhibitors due to poor minimum inhibitory concentrations (MICs); however, it was suggestive that with certain modifications, new series of the inhibitors can be designed.…”
Section: Introductionmentioning
confidence: 97%
“…Mutational studies have shown that the MetAP gene is essential for survival in bacteria [8,9] and cell proliferation in eukaryotes [1012]. In various reports, inhibitors of MetAPs have been identified as potential anticancer [1,13,14], antimalarial [15,16], antibacterial [17,18] and anti-obesity [19,20] drugs. Due to the fact that bacteria contain a single distinct class (Type I) of the enzyme as opposed to those present in eukaryotes (Types I and II), there has been interest in designing isozyme selective inhibitors against bacterial MetAP as desirable antibiotic agents.…”
Section: Introductionmentioning
confidence: 99%
“…During a routine test of target compounds and intermediates synthesized in our laboratory, we discovered that four tricyclic thiazoles— 3 , 7 , 9 , and 11 (Table 1)—were moderately antiproliferative against human umbilical vein endothelial cells (HUVEC) in a [ 3 H]-thymidine incorporation assay In fact, these tricyclic thiazoles had been synthesized in the course of our development of methionine aminopeptidase (MetAP) inhibitors as antimycobacterial agents. 7 It has been established earlier using fumagillin that inhibition of human MetAP2 leads to the growth inhibition of HUVEC. 8,9 However, tricyclic thiazoles 3 , 7 , 9 , and 11 did not inhibit (up to 20 μM) either isoforms of human MetAPs (hMetAP1 and hMetAP2), suggesting that HUVEC inhibition proceeded through a different mechanism.…”
mentioning
confidence: 99%
“…The tricyclic thiazoles were synthesized as per our earlier procedure 7 using a variation of Hantzsch thiazole synthesis. Two typical examples are shown in Scheme 1.…”
mentioning
confidence: 99%